Risky sexual practice and associated factors among antiretroviral therapy attendees in public health facilities, Wolaita Zone, South Ethiopia: a multi-center cross-sectional study - Salato, Sisay Petros; Besha, Befekadu Bekele; Amele, Esayas Aydiko; Abiso, Temesgen Lera (Frontiers in Reproductive Health, 2024)
BackgroundThe majority of people living with Human Immunodeficiency Virus (HIV) are in low- and middle-income countries, particularly in sub-Saharan Africa. Increased risky sexual practice puts people living with the human immune virus at higher risk of acquiring sexually transmitted infections other than the human immune virus and unplanned pregnancies. Sexually transmitted infections, particularly viral hepatitis (B and C), significantly impair antiretroviral therapy and the clinical outcome of the co-infected individual, leading to increased morbidity and mortality. The purpose of this study was to investigate the prevalence of risky sexual practices among antiretroviral therapy (ART) attendees in public health facilities within the Wolaita Zone of South Ethiopia.MethodsFrom September to October 2023, a facility-based cross-sectional study was conducted among adult people living with HIV on ART in the Wolaita zone. Data was collected through a pretested and structured questionnaire. Six diploma nurses were trained to collect data. Systematic sampling techniques were used to select a total of 398 ART patients. Data were collected by Open Data Kit (ODK) and analyzed with SPSS Version 25. Binary and multiple logistic regression analyses were used. All the variables with a P-value of 0.25 associated with risky sexual practices are considered candidate variables. Multicollinearity was checked. The fitness of the model was tested by the Hosmer-Lemshow goodness of fit test. Finally, statistical significance was declared at a p-value of 0.05.ResultA total of 398 respondents took part in this study. The prevalence of risky sexual practices in the past six months was 174 (43.7%) at 95% of the CI (38.9–48.7). The result of multiple logistic regression analysis showed that not disclosing HIV status (AOR = 1.8, 95% CI: 1.1–3.31), alcohol drinking (AOR = 3.1, 95% CI: 1.66–0.023), and poor social support (AOR = 1.9, 95% CI: 1.75–3.9) were statistically significantly associated with risky sexual practices.ConclusionThis study revealed that the risky sexual practice among ART clients was high and disclosure status, social support, and alcohol use were factors associated with risky sexual practice. The governmental and non-governmental bodies have to strengthen social support for ART clients, disclosure status for ART clients, and counseling to avoid alcohol.